INTEGRATING ISLAMIC VALUES IN BUILDING INDEPENDENCE AND MORALITY IN CHILDREN IN THE ERA OF RAPID TECHNOLOGICAL DEVELOPMENT - St. Rahmah; Al-Amin (Indonesian Journal of Education (INJOE), 2025)
Rapid technological developments have brought significant changes to children's learning patterns, behaviour, and character. Although these developments open up great opportunities to expand knowledge and skills, challenges such as moral degradation, declining independence, and exposure to negative content pose real threats. This study aims to analyse strategies for integrating Islamic values in building independence and morality in children in the digital age, using a qualitative descriptive literature review method. Data were obtained from relevant literature, including books, journal articles, and previous studies, which were then analysed using content analysis. The results of the study indicate that Islamic values—such as Amanah (trustworthiness), Tawhid (monotheism), honesty, responsibility, and Ukhuwwah (brotherhood)—play a fundamental role in shaping the character of independent and moral children amid technological advances. The effectiveness of integrating these values is greatly influenced by the involvement of parents, educational institutions, and the social environment through creative and adaptive approaches, such as the use of interactive Islamic digital media, education based on role models, and Islamic digital literacy. This study recommends collaborative strategies that leverage technology as a tool to strengthen Islamic values, enabling children to grow into a generation of intelligent, independent, and morally upright Muslims in the digital age.